Cytopathological evaluation of various thyroid lesions based on Bethesda system for reporting thyroid lesions - Khadatkar, Ashwini S.; Dhume, Varsha M.; Kavishwar, Vikas (International Journal of Research in Medical Sciences, 2017)
Background: An encouragement for the thyroid proposal was the Bethesda system for reporting cervical cytology interpretations, a uniform reporting system for thyroid FNA will facilitate effective communication among health care providers. The objective of the present study was to classify thyroid lesions in various categories under Bethesda system correlating the cytological findings in various thyroid lesions with clinical and radiological details. Methods: A retrospective study on FNAC thyroid was performed in a tertiary hospital and a Medical teaching institution in Mumbai, Maharashtra, India which included cases which were reported from 1st January 2010 to 31st July 2011. For cytomorphological analysis, all smears (Papanicolaou and MGG) were reviewed and cases were categorized into six Bethesda categories. The FNAC findings were correlated with clinical, radiological and laboratory findings. Discrepancies between original diagnosis and review diagnosis as well as difficulties encountered during application of Bethesda were studied in detail. Results: Total 413 FNACs were received during the study period. The original diagnoses included 10 different categories or labels some of which were descriptive. On application of Bethesda, maximum cases were found in category II (82.32%) followed by category I i.e. inadequate (7.7%). Category III (Atypia of Undetermined significance) included wide spectrum of cases which were previously diagnosed as goitre, suspicious or neoplastic. Conclusions: Bethesda system of reporting thyroid FNAC has brought uniformity in cytology reporting. It has facilitated better understanding between cytopathologist and clinicians as every category connotes specific risk of malignancy and recommends treatment.